2023
DOI: 10.1029/2022ja030990
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining Inspired Localized Resistivity in Global MHD Simulations of the Magnetosphere

Abstract: Recent advances in reconstructing Earth's magnetic field and associated currents by utilizing data mining of in situ magnetometer observations in the magnetosphere based on geomagnetic indices and solar wind parameters have proven remarkably accurate at reproducing observed ion diffusion regions. We investigate the effect of placing regions of localized resistivity in global simulations of the magnetosphere at specific locations inspired by the data mining results for the substorm occurring on 6 July 2017. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…More generally, it is also not known how different solar wind parameters will effect the topology of closing reconnection during sub‐Alfvénic solar wind driving. Furthermore, localized resistivity inspired by data mining of observed reconnection locations has been shown to suppress reconnection closer to the Earth (Arnold et al., 2023), which could be an important factor when the tail current sheet retreats toward Earth during the transition from super‐to sub‐Alfvénic solar wind.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, it is also not known how different solar wind parameters will effect the topology of closing reconnection during sub‐Alfvénic solar wind driving. Furthermore, localized resistivity inspired by data mining of observed reconnection locations has been shown to suppress reconnection closer to the Earth (Arnold et al., 2023), which could be an important factor when the tail current sheet retreats toward Earth during the transition from super‐to sub‐Alfvénic solar wind.…”
Section: Discussionmentioning
confidence: 99%
“…Ouellette et al (2010) used GAMERA and found during northward IMF that the reconnection location was not the same as OpenGGCM simulations using an explicit constant resistivity (Dorelli et al, 2007). Explicit resistivity is an available option for the GAMERA simulations, as Arnold et al (2023) used a data-inferred resistivity to incite reconnection in empirically-specified locations. But, a reason to favor the numerical resistivity for this study is that the highest resolution in these simulations is ∼600 km, approaching ion kinetic scales at the magnetopause [∼200 km (Burch et al, 2016a)].…”
Section: Simulation Modelmentioning
confidence: 99%